The Role of Principal’s Power and Teacher Empowerment - Elmazi, Erida (European Scientific Journal, ESJ, 2018)
Principals are a key factor on various aspects of schooling, and teachers play a determinant role on student’s achievement. Several statistical studies have shown this significance. Fewer findings are about the power relationship that exists between the principal and the teachers. The role of effective use of power and empowerment initiatives is not clear. This paper focuses on investigating the relationship among the principal’s bases of power, and the role of power in effective teacher and teacher empowerment. For the current study, the primary data source used was a survey. The sample comprised of 20 principals and 100 teachers in High Schools in Albania. Results of the study indicate that correlation exists between ‘‘staying on top’’ and level of power. Findings show also that there does not exist a general organizational climate that encourages empowerment and delegation The data suggests that most teachers perceive their principals as operating from a legitimate power base.